Mechanical performance evaluation of concrete made with recycled ceramic coarse aggregates from industrial brick waste - Nepomuceno, Miguel (2018)
This paper describes an experimental research that aimed to evaluate the mechanical performance of concrete made with recycled ceramic coarse aggregates from industrial brick waste. Concretes incorporated natural fine aggregates (NFA), natural coarse aggregates (NCA) and the ceramic recycled coarse aggregates (RCA). The aggregates were characterized by particle size distribution, flakiness index, shape index, particle density, water absorption, loose bulk density, voids, crush resistance and resistance to fragmentation. Once the aggregates were studied, concretes were produced with RCA replacing NCA in absolute volume percentages of 0%, 10%, 30%, 50% and 75%. All the concretes were produced with the same workability and aggregate size gradation. In the hardened state, concretes were evaluated by the compressive strength, flexural strength, tensile splitting strength and density. The results showed the feasibility of partial replacement of NCA by RCA, despite the mechanical performance of concrete decreases with increasing replacement of NCA by RCA.